Kesetaraan dan Keadilan dalam Islam: Tinjauaan Hasil Konferensi CEDAW tentang Feminisme berdasarkan Karakteristik Islam - Endang Saptorini (PKP Pusat Jurnal LPPM IAi Nasional Laaroiba, 2024)
This paper aims to examine the concept of equality and justice in the characteristics of Islamic teachings as a review of the results of the CEDAW conference on feminism. The conclusion of the theoretical study is that Islamic teachings place equal positions between men and women in religion, worship, law, economy, and social society in accordance with the nature set by Allah to him. Equality by prioritizing justice makes life peaceful and prosperous, thus proving that Islamic teachings are a blessing for all nature.